Politic and Islam: A Systematic Literature Review: whether politics and Islam can develop simultaneously - siti maisyaroh siti maisyaroh (UIN Mataram, 2022)
This study aims to find out issues regarding politics and Islam in the world. The research method applied to this study is a systematic literature review that uses 256 scientific articles sourced from the Scopus database. Review the article using the Vos viewer application. The results of the study based on the evidence of the Scopus database literature reveal the development of Islam in the political arena is very interesting to study, from several studies on the politics of Islam in politics. The results of this study contribute to developing a research roadmap on Islamic political issues. The limitation of this study is that the article used is only sourced from the Scopus database so the research findings cannot describe comprehensively the political problems of Islam. The following research needs to use scientific articles from other reputable international data, such as the web of Science Dimensions Scholars. Keywords: politic, Islam, international, development